Rankings of tuberculosis antibiotic treatment regimens are sensitive to spatial scale, detection limit, and initial host bacterial burden - Christian T. Michael; Maral Budak; Pauline Maiello; Kara Kracinovsky; Mark Rodgers; Jaime Tomko; Philana Ling Lin; JoAnne Flynn; Jennifer J. Linderman; Denise Kirschner (Journal of Theoretical Biology, 2025)

The best of both worlds: Why antipredator traits are lost in predator-free havens and how to keep them - Natasha R. LeBas; Jennifer Rodger; Rowan A. Lymbery; Joseph L. Tomkins; Dominique Blache (Biological Conservation, 2025)

A repeated measures cognitive affective bias test in rats: comparison with forced swim test - Benjamin Aliphon; Twain Dai; Jessica Moretti; Marissa Penrose-Menz; Wilhelmina H. A. M. Mulders; Dominique Blache; Jennifer Rodger (Psychopharmacology, 2023)

The effect of a digital health coaching and health education protocol on cognition in adults at-risk for Alzheimer’s - Anthony Campitelli; Joshua L. Gills; Megan D. Jones; Sally Paulson; Jennifer Myers; Kelsey Bryk; Erica N. Madero; Jordan M. Glenn; Charlie H. Rodgers; Jenova A. Kempkes; Michelle Gray (GeroScience, 2023)
Several modifiable lifestyle factors have been linked to cognitive ability and the risk of developing Alzheimer’s disease and related dementias (ADRD). Health coaching (HC) is an intervention that addresses lifestyle factors associated with cognition. The effectiveness of an HC protocol was evaluated and compared with a health education (HE) intervention, representing the current standard of care, in a sample of 216 adults between the ages of 45 and 75 years who were at-risk for developing ADRD. Outcomes examined were global cognition, neuropsychological cognition, and Alzheimer’s risk. HC participants received personalized coaching from a health coach focusing on nutrition, physical activity, sleep, stress, social engagement, and cognitive activity. HE participants received biweekly education materials focusing on the same modifiable lifestyle factors addressed by HC. Participants were assessed at baseline and again 4 months later. Self-reported global cognition scores improved only in the HC group (16.18 to 15.52, p = .03) and neuropsychological cognitive ability improved in the HE group (104.48 to 108.76, p < .001). When non-adherence in the HC group was accounted for, however, the mean change in neuropsychological score was similar between groups ( p > .05), self-reported global cognition demonstrated an even larger mean improvement in the HC group (16.20 to 15.41, p = .01), and the HC group saw an improvement in ADRD protective risk score (− 10.39 to − 11.45, p = .007). These results indicate that HC and HE can both improve cognition, but HC may be more effective and may yield increased protection against ADRD risk.

Social-ecological change in the Omo-Turkana basin: A synthesis of current developments - Jennifer Hodbod; Edward G. J. Stevenson; Gregory Akall; Thomas Akuja; Ikal Angelei; Elias Alemu Bedasso; Lucie Buffavand; Samuel Derbyshire; Immo Eulenberger; Natasha Gownaris; Benedikt Kamski; Abdikadir Kurewa; et al. (Ambio, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Comparison of ion channel inhibitor combinations for limiting secondary degeneration following partial optic nerve transection - Lillian M. Toomey; Carole A. Bartlett; Maimuna Majimbi; Gopana Gopalasingam; Jennifer Rodger; Melinda Fitzgerald (Experimental Brain Research, 2019)

Species and Genotype Effects of Bioenergy Crops on Root Production, Carbon and Nitrogen in Temperate Agricultural Soil - Andrew S. Gregory; Jennifer A. J. Dungait; Ian F. Shield; William J. Macalpine; Jennifer Cunniff; Mark Durenkamp; Rodger P. White; Adrian Joynes; Goetz M. Richter (BioEnergy Research, 2018)

Design and Performance of Pilot-Scale Constructed Wetland Treatment Systems for Treating Oilfield Produced Water from Sub-Saharan Africa - Jennifer E. Horner; James W. Castle; John H. Rodgers; Cynthia Murray Gulde; James E. Myers (Water, Air, & Soil Pollution, 2012)

Intact amino acid uptake by northern hardwood and conifer trees - Anne Gallet-Budynek; Edward Brzostek; Vikki L. Rodgers; Jennifer M. Talbot; Sharon Hyzy; Adrien C. Finzi (Oecologia, 2009)

Effects of trkB knockout on topography and ocular segregation of uncrossed retinal projections - Jennifer Rodger; Douglas O. Frost (Experimental Brain Research, 2009)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

Graded ephrin-A2 expression in the developing hamster superior colliculus - Sherralee S. Lukehurst; Carolyn E. King; Lyn D. Beazley; David K. C. Tay; Kwok-Fai So; Jennifer Rodger (Experimental Brain Research, 2006)